Taxonomy of the Paramekongiella (Orthoptera: Pyrgomorphidae) with description of a new species - Yu, Hong-Lei; Huang, Zhi-Pang; Wang, Xun; Li, Fang-Ting; Mao, Ben-Yong (Zootaxa, 2025)
A supplemented description of Paramekongiella morphology and a redescription Paramekongiella zhongdianensis are provided based on topotypes with photographs. A new species of Paramekongiella muliensis Mao et Huang sp. nov. is described and illustrated. An updated species key for Paramekongiella is provided. The tegmina and tympanal organs among five allied genera are compared.